Total quality management and changes in management accounting systems in a manufacturing firm: a case study / Sachini Ishanka and Tharusha Gooneratne. - Ishanka, Sachini; Gooneratne, Tharusha (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2018)
This paper explores the emergence of Total Quality Management (TQM), its continuation as well as the management accounting implications in a leading solid tyre manufacturing firm in Sri Lanka, where TQM has been practiced for over fifteen years. The paper adopts the qualitative methodology and case study approach, while the rational-choice perspective and new institutional sociology have been utilized as the theoretical lens. Our findings suggests that both institutional as well as technical efficiency reasons have influenced the implementation of TQM, and that the management accounting system of the firm has been changed to keep up with the TQM system. How management accounting systems get implicated in a TQM environment, although important has received limited research interest; thus this research is a useful addition to the existing literature. This paper also has theoretical merits; it depicts how coming together of a rational-choice perspective and new institutional sociology provides a better understanding on internal and external reasons for implementing management tools (such as TQM). Using a TQM example, our paper provides learning points to practicing managers on how management accounting systems could be shaped to facilitate implementation of management tools.